PENDAMPINGAN PEMBUDAYAAN NILAI PANCASILA DALAM PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH LABORATORIUM - Maisyaroh, Maisyaroh; Untari, Sri; Chusniyah, Tutut; Adha, Maulana Amirul; Prestiadi, Dedi; Saputra, Bagus Rachmad; Yulaidi, Endrik Mas (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
There is a degradation of values ??and morals in the midst of a massive era of change, efforts are needed to fortify students with the civilizing of Pancasila values ??in order to create students with character. The purpose of this activity is to provide new insights and skills for school principals and teachers in cultivating Pancasila values as the basis for the value of strengthening students character in schools through fostering students and structuring school infrastructure. The activity was carried out at the Laboratory Elementary School, Universitas Negeri Malang, Blitar, using a training and mentoring approach. Evaluation of activities using pre-test and post-test instruments were analyzed using a descriptive quantitative technique. As per the findings of the evaluation, it showed an increase in participants' insight and skills in strengthening character education based on Pancasila values, indirectly this training and mentoring activity also had a positive impact on increasing participants' motivation to realize Pancasila-based schools